Disappointment and Identity Upheaval in the Sun also Rises: Exploring the Impact of War on Personal Identity (Journal of Advances and Scholarly Researches in Allied Education, 2020)
No American writer is more associated with writing about war in the early 20th century than Ernest Hemingway. He experienced it firsthand, wrote dispatches from innumerable frontlines, and used war as a backdrop for many of his most memorable works. During the First World War, Ernest Hemingway volunteered to serve in Italy as an ambulance driver with the American Red Cross. His war experience had changed him dramatically.